2009
DOI: 10.1557/jmr.2009.0061
|View full text |Cite
|
Sign up to set email alerts
|

Growth of nanotubes in sol-gel-derived V2O5 powders and films prepared under acidic conditions

Abstract: The structural evolution with temperature of some V2O5 gels and thin films is presented, and the role of the hydrolysis conditions is investigated. Several techniques, i.e., x-ray diffraction, differential thermal analysis, infrared, and temperature-dependent Raman spectroscopy, have been used to follow the thermal behavior of the samples. When the bulk xerogels begin to change from a nanocrystalline phase to the orthorhombic α-V2O5, in the temperature range 280 to 300 °C, a growth of vanadium oxide nanotubes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 39 publications
2
12
0
Order By: Relevance
“…The characteristic bands of V 2 O 5 appear in the spectrum of samples treated at 300 • C and become more prominent for the samples annealed at 500 • C. In the high-frequency region, the strong band at 1006 cm −1 corresponds to the V=O stretching vibration of the vanadyl unshared oxygen, [36][37] coincide with the beginning of the formation of the nanostructures. 39 Our Raman results on the crystallization are in agreement with XRD data on the sol-gel films. [40][41] Effect of heat-treatment on the electrochromic properties of vanadium pentoxide thin films.-The electrochromic properties of the films were studied as a function of their thickness and annealing temperature.…”
Section: Resultssupporting
confidence: 87%
“…The characteristic bands of V 2 O 5 appear in the spectrum of samples treated at 300 • C and become more prominent for the samples annealed at 500 • C. In the high-frequency region, the strong band at 1006 cm −1 corresponds to the V=O stretching vibration of the vanadyl unshared oxygen, [36][37] coincide with the beginning of the formation of the nanostructures. 39 Our Raman results on the crystallization are in agreement with XRD data on the sol-gel films. [40][41] Effect of heat-treatment on the electrochromic properties of vanadium pentoxide thin films.-The electrochromic properties of the films were studied as a function of their thickness and annealing temperature.…”
Section: Resultssupporting
confidence: 87%
“…However, there is a great similarity with the patterns of V 2 O 5 ·nH 2 O xerogel (PDF 40-1296) with the difference that our patterns exhibit additional peaks. From the literature survey on vanadium oxides [6,[26][27][28][29] it is well known that the X-ray patterns of V 2 O 5 ·nH 2 O xerogel are characterized by a small number of 3-5 broad peaks from the series of 00l reflections (missing 002 peak). Moreover, the intensity of the first order diffraction 001 located generally around d = 11.5 Å is much larger than that of the other terms.…”
Section: Composition and Structure Of The Thin Filmsmentioning
confidence: 99%
“…26 This determines the typical XRD pattern of the xerogels that is characterized by a small number of 3-5 broad peaks from the series of 00l reflections (missing 002 peak) with a pronounced 001 peak located generally around 11.5 Å. 5,13,28 It was reported that the intercalation of cations like Na + and TMA + (tetramethyl ammonium) into the xerogel leads to the appearance of extra diffraction peaks in the diffraction patterns of M 0.3 V 2 O 5 •1.5H 2 O. 25 Durupthy et al 25 have suggested that the observation of hkl set of reflections (instead of 00l only) is related to the loss of ordered stacking of the double V 2 O 5 layers.…”
Section: Resultsmentioning
confidence: 99%
“…10,11 Most recently, Costa et al reported that the electrochromic cell based on an inkjet printed vanadium oxide xerogel on flexible PET/ITO electrode exhibits excellent colour contrast between different redox states and excellent cycling stability (more than 30 000 cycles with a degradation of 18%) which characteristics make it very promising for application in intelligent windows. 2 Vanadium(V) oxide xerogels (solids and thin films) are most often prepared by sol-gel method in three main variants (using three synthetic routes): acidification of metavanadate aqueous solutions, 5,10,12 hydrolysis condensation of alkoxides 5,7,13,14 and reaction between H 2 O 2 and V 2 O 5 powder. 2,15 a Other methods such as hydrothermal, 16 sputtering, 17,18 electrodeposition, 19 laser ablation techniques, 20 inkjet printing, 2 etc.…”
Section: Introductionmentioning
confidence: 99%